Preclinical characterization of a novel investigational monoclonal antibody CM313 with potent CD38-positive cell killing activity - Liu, Wei; Yu, Juntao; Sun, Kaiwen; Song, Qin; Li, Yuling; He, Yanyun; Wang, Yanrong; Xu, Gang; Wang, Changyu; Chen, Bo (Frontiers in Immunology, 2024)
CM313 is currently under clinical investigation for treatments of multiple myeloma, systemic lupus erythematosus, and immune thrombocytopenia. We aimed to report the preclinical profile of the novel therapeutic anti-CD38 monoclonal antibody (mAb) CM313, with an emphasis on the difference with other CD38-targeting mAb. There exist unique sequences at complementaritydetermining regions (CDR) of CM313, which facilitates its affinity to CD38 is consistently higher across a spectrum of CD38 + cell lines than daratumumab. In vitro studies showed that CM313 induces comparable killing activity than daratumumab, including ADCC, CDC, ADCP, apoptosis induced by Fc-mediated cross-linking, and effectively inhibited the enzymatic activity of CD38.However, CM313 showed more potent CDC than isatuximab. In vivo, CM313 dose-dependently inhibited xenograft tumor growth, both as a monotherapy and in combination with dexamethasone or lenalidomide. Furthermore, CM313 was well tolerated with no drug-related clinical signs or offtarget risks, as evidenced by 4-week repeat-dose toxicology studies in cynomolgus monkeys and B-hCD38 mice, with the later study showing no observed adverse effect level (NOAEL) of 300mg/kg once weekly. Thus, our finding identifies CM313 as a novel investigational humanized mAb with a distinct CDR sequence, showing comparable killing effects with daratumumab and stronger CDC activity than isatuximab, which supports its clinical development.